Adaptasi Mahasiswa Baru dalam Perkuliahan (Studi Kasus Tadris Bahasa Inggris STAIN Majene) - Wahyuddin; Tria Nurwahda AR (Institute of Computer Science (IOCS), 2022)
This study aims to reveal the experience of adaptation of new students of English Language Tadris (TBI) STAIN Majene regarding lectures. This research is a qualitative study using a phenomenological approach. A total of four new students were recruited as participants. The selection of subjects was based on the purposive principle, which was chosen at the beginning on the consideration that they had experienced the phenomenon under study. Data were collected through semi-structured interview techniques and observation to get a direct picture of how the informants adapted. The data were analyzed descriptively qualitatively by presenting the data in a structured manner through conceptualization, classifying, categorizing, identifying themes, and then connecting them with theoretical constructs. The results showed that new students of the TBI STAIN Majene study program had different feelings and adaptations when entering the campus world. Some adapt easily and some find it difficult. Factors that influence their adaptation are readiness, previous college experience, and perception of the academic world of higher education.